KELEMBAGAAN LAHAN KOMUNAL UNTUK PENGEMBANGAN TERNAK DI NTB (KASUS KABUPATEN SUMBAWA) - Mashur, Mashur (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
Utilization of communal land in NTB about 20% and still available 80% for the development of livestock business. Therefore, communal land has weaknesses, especially in the provision of feed in the dry season, and lack of local government support in land use as a basis for livestock development. This study aims to determine the utilization of pastures, cattle rearing patterns, and government support in the development of cattle breeding. The study was conducted in Sumbawa Regency in October 2013 through a survey. The results show that some communal land has not been utilized for livestock development, and there is a reduction in pasture land as it is converted to agriculture. Communal land management is not maximized and has an impact on the lack of feed in the dry season. The pattern of livestock raising is still traditional. As a result, low productivity and increased mortality. Local institutional support and local government policy for communal land use for livestock development is relatively low. To improve the productivity of livestock, it is necessary to change the pattern of maintenance through the development of forage feed.